Medio ambiente, grupos sociales y conocimiento local en la dehesa. Un caso de estudio en la Sierra Morena extremeña - Acosta Naranjo, R (Revista Española de Estudios Agrosociales y pesqueros, 2005)
The changes in rhe economic strategies, management models and productive uses in the dehesa haie caused very differenr effects regarding the state of the ñatu¡al ¡esources, The limits to the norm of intensification and use of technology in an agricultural ecosystem with slrong socio-econornic and natural restrictions have had as a consequence the end of a series of tasks that can have degrading effects on the natu¡al resources and a possible chan- ge to more mature states $'ithin rhe ecosystem. This fact takes into account the nature buil- ding proc€ss, of "naturalization. in marginal zones, that can be found in contemporary sociéties. On the other hand, those same f¿cts can be interpreted as a degr¿dation of the productive resources. However, the social actors do not perceive as enüronmental problems the rnajority ofphenomena defined as such by üe specialists. The spatjal sPecializalion pro' cesses ánd territorial uneven development can also be observed in üe dehesa. Finall¡ one of the main consequences of the changing process has been the strong dete¡ioration of local knowledge.
Keywords: Dehesa; environmental enthropology; local knowledge; traditional agroecosistems degradation

Medio ambiente, grupos sociales y conocimiento local en la dehesa. Un caso de estudio en la Sierra Morena extremeña - Acosta Naranjo, R. (Revista Española de Estudios Agrosociales y pesqueros, 2005)
The changes in rhe economic strategies, management models and productive uses in the dehesa haie caused very differenr effects regarding the state of the ñatu¡al ¡esources, The limits to the norm of intensification and use of technology in an agricultural ecosystem with slrong socio-econornic and natural restrictions have had as a consequence the end of a series of tasks that can have degrading effects on the natu¡al resources and a possible chan- ge to more mature states $'ithin rhe ecosystem. This fact takes into account the nature buil- ding proc€ss, of "naturalization. in marginal zones, that can be found in contemporary sociéties. On the other hand, those same f¿cts can be interpreted as a degr¿dation of the productive resources. However, the social actors do not perceive as enüronmental problems the rnajority ofphenomena defined as such by üe specialists. The spatjal sPecializalion pro' cesses ánd territorial uneven development can also be observed in üe dehesa. Finall¡ one of the main consequences of the changing process has been the strong dete¡ioration of local knowledge.
Keywords: Dehesa; environmental enthropology; local knowledge; traditional agroecosistems degradation